Primary Adenoid Cystic Carcinoma, Subtype of Ceruminous Adenocarcinoma in Right External Auditory Canal: a Case Report - Eka Putra Pratama; Susilawati; Wresnindyatsih (Jurnal RSMH Palembang, 2021)
Background. Ceruminous adenocarcinoma is rare, accounting for less than 2,5% of all external auditory canal neoplasms. The tumours occur in the outer half of the external auditory canal, excluding direct extension from parotid gland. Adenoid cystic carcinoma is the most common subtypes. Adenoid cystic carcinoma needs to be distinguished from its primary origin from the salivary glands and extends to ear, because they share the same histopathology features and immunohistochemistry. Therefore, combinations of clinical features and radiology is needed to diagnose this tumour correctly.Case description. A female patient, 60 years old, admitted to RSMH Palembang with complaint ofyellow discharge coming out from ear. She also havehearing loss and pain since 6 months before admission to the hospital. One week later, the patient develops facial weakness with no mass on face. CT-Scan examination was performed, with the results showed that the mass in right external auditory canal and extends to the mastoid cavity, maxillary sinus wall and brain parenchym. Biopsy was performed in mastoid region and revealed tumour mass with cribriform pattern, few solid pattern, consists of bilayered neoplastic cells with inner luminal and outer abluminal cells. Immunostaining showed CK7 and CD117 positive in luminal cells, p63 positive in abluminal cells, S100 showed positivity in myoepithelial cells.Discussion and conclusion. Based on clinical symptoms, radiology, histopathology, and imunohistochemical staining, the mass in right mastoidis consistent with a ceruminous adenocarcinoma, adenoid cystic carcinoma subtypes, originated from external auditory canal.